The Masjid-Based Community Economic Empowerment - Mu'is, Ahmad Mu'is (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2020)
Social Empowerment in rural society of Malang Village or local economic base on Masjid is community dedication configuration. This place has potential capital field and human resources development. The job of coomunity majority are farmers. The field has been planted by holticulture variety while human resourses are religious community. The weaknesss are knowledge and ability to develop their village. The struggle of this empowerment is giving technical knowledge and skill of economic basic, for instance management, accounting and marketing. The methode of this researh is base on participation action research (PAR) in order to get deep information and participation from rural society. Masjid as fundamental factor to motivate and guide them to better human.